The Effect of Service Quality on Return Interest at Piru Hospital, West Seram Regency - Sunik Cahyawati; Herlien Sinay; Noer Mahriana Hakim; Dian Ely (Journal of Health Sciences, Medicine, Biotechnology, and Pharmaceutical Research, 2025)
Hospitals are an internal part of the health service system. In Indonesia, all public and private hospitals have the duty to carry out curative and rehabilitative efforts without neglecting preventive and promotive efforts as well as making referral efforts. Patients have the right to obtain quality health services in accordance with professional standards and standard operational procedures so that hospitals are always required to improve the quality of service. The aim of this research is to determine the influence of the quality of health services on interest in returning to Piru Hospital, West Seram Regency. This research method is quantitative using a cross sectional approach. The sample in this study consisted of 30 respondents according to Sugiyono 2019:127. This research instrument uses a questionnaire. Data processing uses SPSS, using the chi-square test with a significance level of (0.05). The results of the research on the influence of health service quality on return interest showed that the p value was <0.000 with (α<0.05), meaning there was a significant relationship between the influence of health service quality on return interest at Piru District Hospital. . The results of research on the influence of health service quality on interest showed that the p value was > 0.05 with (α > 0.05), meaning there was no significant relationship.